Decoy Receptor 3 Promotes Preosteoclast Cell Death via Reactive Oxygen Species-Induced Fas Ligand Expression and the IL-1α/IL-1 Receptor Antagonist Pathway. (10th June 2020) - Peng, Yi-Jen; Peng, Ching-Tsung; Lin, Yi-Hsuan; Lin, Gu-Jiun; Huang, Shing-Hwa; Chen, Shyi-Jou; Sytwu, Huey-Kang; Cheng, Chia-Pi
Abstract : Purpose . Interleukin-1 α (IL-1 α ) is a potent cytokine that plays a role in inflammatory arthritis and bone loss. Decoy receptor 3 (DCR3) is an immune modulator of monocytes and macrophages. The aim of this study was to investigate the mechanism of DCR3 in IL-1 α -induced osteoclastogenesis. Methods . We treated murine macrophages with DCR3 during receptor activator of nuclear factor kappa Β ligand- (RANKL-) plus IL-1 α -induced osteoclastogenesis to monitor osteoclast formation by tartrate-resistant acid phosphatase (TRAP) staining. Osteoclast activity was assessed using a pit formation assay. The mechanisms of inhibition were studied by biochemical analyses, including RT-PCR, immunofluorescent staining, flow cytometry, an apoptosis assay, immunoblotting, and ELISA. Results . DCR3 suppresses IL-1 α -induced osteoclastogenesis in both primary murine bone marrow-derived macrophages (BMM) and RAW264.7 cells as it inhibits bone resorption. DCR3 induces RANKL-treated osteoclast precursor cells to express IL-1 α, secretory IL-1ra (sIL-1ra), intracellular IL-1ra (icIL-1ra), reactive oxygen species (ROS), and Fas ligand and to activate IL-1 α -induced interleukin-1 receptor-associated kinase 4 (IRAK4). The suppression of DCR3 during RANKL- or IL-1 α -induced osteoclastogenesis may be due to the abundant secretion of IL-1ra, accumulation of ROS, and expression of Fas ligand in apoptotic osteoclast precursor cells. Conclusions . We concluded that there is an inhibitory effect of DCR3 on osteoclastogenesis via ROS accumulation and ROS-induced Fas ligand, IL-1 α, and IL-1ra expression. Our results suggested that the upregulation of DCR3 in preosteoclasts might be a therapeutic target in inflammatory IL-1 α -induced bone resorption.